Pseudourostyla pelotensis sp. nov. (Ciliophora, Stichotrichia, Urostylida): a new psammophilic ciliate from the southern Brazil - Paiva, Thiago Da Silva; Da Silva-Neto, Inácio Domingos (Zootaxa, 2006)
In samples of sand collected from the Laranjal beach, a lake shore located in the state of Rio Grande do Sul, Brazil, we found a new urostylid species characterized as: Pseudourostyla measuring about 190 x 80 µm in vivo; body very flexible, dorsoventrally compressed in almost 2:1 proportion, with ovoid and ellipsoid colorless cortical granules and displaying a short beak-like projection oriented to the left at the anterior region of the cell. Two contractile vacuoles present. Somatic ciliature with a typical bicorona and urostylid midventral complex formed by cirral pairs, that ends below the equatorial region of the cell. Pre-transverse cirri lacking; on average two frontoterminal cirri, five left and six right marginal cirral rows, six transverse cirri and eight dorsal kineties. Adoral zone composed of about 50 membranelles. Pseudourostyla pelotensis sp. nov. differs from other congeners by the presence of an anterior beak-like projection, two contractile vacuoles instead of one, and a unique combination of other characters including extension of the midventral complex, number of adoral membranelles and of macronuclear nodules.